2018
DOI: 10.1177/2381468317746170
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Midwives’ Preferences for Providing Information About Newborn Bloodspot Screening

Abstract: Background: Understanding preferences for information provision in the context of health care service provision is challenging because of the number of potential attributes that may influence preferences. This study aimed to identify midwives’ preferences for the process and outcomes of information provision in an expanded national newborn bloodspot screening program. Design: A sample of practicing midwives completed a hybrid-stated preference survey including a conjoint analysis (CA) and discrete choice exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…An approach to modernizing the RUSP might include an updated integration and assessment of preferences for NBS. Research has explored preferences for NBS, (Lipstein et al, 2010 ; Miller et al, 2015 ; Tarini et al, 2018 ; Vass, Georgsson, Ulph, & Payne, 2019 ; Wright, Ulph, Dharni, & Payne, 2017 ; Wright, Ulph, Lavender, Dharni, & Payne, 2018 ) however preference assessment is not routinely incorporated into decisions regarding which conditions to include on the RUSP. Evidence gaps exist regarding the role of preferences and NBS programs, including uncertainty regarding how preference information can be integrated into the evidence review process for the RUSP, and how families, professionals, and the public may differently value preference information in the NBS context.…”
Section: Discussionmentioning
confidence: 99%
“…An approach to modernizing the RUSP might include an updated integration and assessment of preferences for NBS. Research has explored preferences for NBS, (Lipstein et al, 2010 ; Miller et al, 2015 ; Tarini et al, 2018 ; Vass, Georgsson, Ulph, & Payne, 2019 ; Wright, Ulph, Dharni, & Payne, 2017 ; Wright, Ulph, Lavender, Dharni, & Payne, 2018 ) however preference assessment is not routinely incorporated into decisions regarding which conditions to include on the RUSP. Evidence gaps exist regarding the role of preferences and NBS programs, including uncertainty regarding how preference information can be integrated into the evidence review process for the RUSP, and how families, professionals, and the public may differently value preference information in the NBS context.…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 28 Four published stated preference surveys were identified that quantified preferences for a NBS program. 20 22 , 29 The candidate attributes selected from these 4 published DCEs, and the qualitative interviews, were the type of treatment available for children with inherited diseases that are detected early by screening, the time from the screening test to diagnosis and the start of treatment, whether the bloodspot was stored or not, and the false-positive rate of screening. Levels for these attributes were assigned based on the potential values for each level seen in current implementations of NBS programs.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the potential role of using non–text-based information strategies was explored in a DCE completed by 800 respondents including parents. 1 , 20 , 21 …”
Section: Methodsmentioning
confidence: 99%
“…Wright et al , in another DCE, investigated information provision among midwives in the UK, when asking them about when to disclose information to expecting parents or what type of information should be provided. 23 According to this study, the potential for receiving a ‘false positive’ result should not be disclosed (as it may not be helping decision-making), and the best period to provide information would be late pregnancy to 3 days post-birth. The current study protocol, 7 years after the first DCEs on the topic in Europe, offers a comparison point for diverse cultural perspectives, attribute importance and technical advances in genetic technique preferences.…”
Section: Introductionmentioning
confidence: 98%
“…Respondents from the general public were positive about the potential for gNBS expansion in the country based on the expected clinical benefits, improvement of reproductive risk management and also the possibility of earlier diagnosis. Wright et al , in another DCE, investigated information provision among midwives in the UK, when asking them about when to disclose information to expecting parents or what type of information should be provided 23. According to this study, the potential for receiving a ‘false positive’ result should not be disclosed (as it may not be helping decision-making), and the best period to provide information would be late pregnancy to 3 days post-birth.…”
Section: Introductionmentioning
confidence: 99%